Hard rock in situ mining. Its application in a copper oxide ore deposit - Ortiz Sánchez, Oswaldo (2010)
In situ metalic mining are sistems of metal elements recovery through leaching at their primary emplacements in hard rock ore deposits by appropriate chemical solutions. The methods involve recuperation of metals from ore bodies by circulating solutions through the ore in its undisturbed geologic state and recovering these solutions for processing. In order to attain acceptable orebody permeability for flowing of leach solutions, fragmentation is a basic variable. It should be obtained by drilling and blasting with explosives or by hydrofracturing. Examples are some Southern USA in situ mining operations where rock fragmentation with explosives was succesfully tried in coyote holes or open pit blasting grids. Other significant in situ mining variables are the mineral geologic genesis which works in opposite direction to the insitu leach treatment, the natural rock porosity, the ore left insitu by previous mining exploitation, the unstable rock mass underground, the ore located very deep underground. Costs for gaining this ore are prohibited the only possibility of economic recovery being insitu mining by leach solutions in long hole drilling and conventional mine drives. In this study in situ mining is applied to abandoned oxide copper ore reserves left by the underground mining of a copper ore body which is being exploited for over forty eigth years.